Near unity emissivity thermal radiator

CN122952541APending Publication Date: 2026-10-20CITY UNIVERSITY OF HONG KONG
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610463506.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-10
Filing Date
2026-04-09
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

尽管这些加工方法已相当成熟,但加工成本依然较高,且结构复杂度受限于加工技术

Benefits of technology

[0030]上述概述既不旨在界定本申请的发明(其范围由权利要求限定),也不旨在以任何方式限制本发明的范围。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a patterned heat sink comprising a polymer film and a first microscale surface structure formed on the polymer film. Utilizing micro-3D printing technology, this heat sink achieves near-unit emissivity (>0.99) within an atmospheric window. Integrating this heat sink into an LED lighting system can significantly reduce its temperature and increase its brightness, demonstrating its promising application in the field of thermal management for electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to thermal radiators, such as radiant coolers for electronic products. Background Technology

[0002] With the development of semiconductor technology, the integration of electronic products is constantly increasing, and their power consumption is also increasing accordingly. For example, the luminous efficacy of LEDs is about 60%, which means that in addition to emitting light, nearly half of the energy is consumed as heat. To ensure that the temperature rise caused by heat generation does not affect the normal operation of electronic devices, thermal management of electronic products has become one of the most important considerations in product design. Typically, the size of the heat dissipation module of an electronic product directly determines its final size, thus affecting material, warehousing, and transportation costs. Therefore, finding efficient and compact heat dissipation solutions is crucial. Radiative cooling is an ideal thermal management solution because it is a passive heat dissipation method that requires no additional energy. Radiative cooling technology utilizes the high thermal radiation characteristics of radiative cooling materials in the long-wave infrared band to radiate heat to outer space at a temperature of approximately 3 K. This allows objects to be cooled without additional energy. According to the Stefan-Boltzmann law, the thermal radiation power is... , in , , , These represent surface area, emissivity, Stefan-Boltzmann constant, and temperature, respectively. Clearly, thermal radiation power is positively correlated with the temperature, surface area, and emissivity of the radiation source. Note that emissivity... It is the launch angle. θ and wavelength λ The emissivity is a function of the atmospheric window (8–13 µm). To achieve optimal thermal radiation performance, the thermal radiator (or radiative cooler) must reach unity emissivity at all angles within this atmospheric window. Therefore, the goal is to get as close to this emissivity limit as possible.

[0003] Metamaterials are an important choice for achieving high-performance thermal radiators because their radiation characteristics (including bandwidth and emissivity) can be artificially tunable. Raman et al. prepared a seven-layer HfO2-SiO2-HfO2 thin film on Ag thin film; these dielectric layers were designed to effectively emit infrared radiation through phonon-polaron resonance and interference effects. Chae et al. designed a simple multilayer structure cooler composed of inorganic materials such as Al2O3, Si3N4 and SiO2, which showed excellent radiation performance in the 8–13 µm wavelength range

[24] . The obtained inorganic thermal radiator had an average emissivity of 87% in the 8–13 µm band and an average absorptivity of 5.2% in the solar spectral region (0.3–2.5 µm). Although one-dimensional metamaterial design has significant advantages in selective radiative cooling, few studies have achieved extremely high emissivity. Hossain et al. first used an anisotropic conical metamaterial column composed of seven periodically alternating metal / dielectric layers ( Figure 3c High-efficiency selective radiators were fabricated within an atmospheric transparent window [2]. However, the fabrication of such multilayer stacked structures with variable cross-sections is difficult and costly. Zhang et al. mixed Al2O3 into PDMS to fabricate pyramid-shaped surface microstructures

[20] . This artificial layered structure exhibits high emissivity (96%) and high solar reflectivity (95%). Although its infrared emission performance is good, it has not yet reached the theoretical limit. In contrast, Song et al. fabricated an atmospheric window ultra-high emissivity cavity resonant structure based on a two-dimensional grating

[16] . Although an emissivity close to 1 was achieved, the angular dependence of the emissivity was not explored, and columnar structures are generally not good at omnidirectional emission. The metamaterials described in the above studies are mainly processed by methods such as vapor deposition and photolithography. Although these processing methods are quite mature, the processing cost is still high, and the structural complexity is limited by the processing technology. In summary, there is an urgent need to propose a radiation cooler that is easy to process and has omnidirectional ultra-high emissivity.

[0004] References The following references are cited in this specification, indicated by numbered square brackets. For all purposes, the entire contents of each of these references are incorporated herein by reference.

[0005] [1] Hervé, A.; Drévillon, J.; Ezzahri, Y.; Joulain, K. Radiativecooling by tailoring surfaces with microstructures: Association of a gratingand a multi-layer structure. Journal of Quantitative Spectroscopy and Radiative Transfer2018, 221 , 155-163. DOI: 10.1016 / j.jqsrt.2018.09.015. [2] Hossain, M. M.; Jia, B.; Gu, M. A Metamaterial Emitter for HighlyEfficient Radiative Cooling. Advanced Optical Materials 2015, 3 (8), 1047-1051.DOI: 10.1002 / adom.201500119. [3] Jeon, D. J.; Ji, S.; Lee, E.; Kang, J.; D'Alba, L.; Shawkey, M.D.; Yeo, J. S. How the Eurasian Jay Expands its Color Palette by OptimizingMultiple Scattering. Advanced Optical Materials 2022, 11 (4). DOI: 10.1002 / adom.202202210. [4] Jeong, S. Y.; Tso, C. Y.; Wong, Y. M.; Chao, C. Y. H.; Huang, B.Daytime passive radiative cooling by ultra emissive bio-inspired polymericsurface. Solar Energy Materials and Solar Cells 2020, 206 . DOI: 10.1016 / j.solmat.2019.110296. [5] King, J.; Wan, C.; Park, T. J.; Deshpande, S.; Zhang, Z.;Ramanathan, S.; Kats, M. A. Electrically tunable VO2–metal metasurface formid-infrared switching, limiting and nonlinear isolation. Nature Photonics 2023. DOI: 10.1038 / s41566-023-01324-8. [6] Kusunoki, F.; Kohama, T.; Hiroshima, T.; Fukumoto, S.; Takahara,J.; Kobayashi, T. Narrow-Band Thermal Radiation with Low Directivity byResonant Modes inside Tungsten Microcavities. Japanese Journal of Applied Physics 2004, 43 (8R). DOI: 10.1143 / jjap.43.5253. [7] Lee, E.; Luo, T. Black body-like radiative cooling for flexiblethin-film solar cells. Solar Energy Materials and Solar Cells 2019, 194 , 222-228. DOI: 10.1016 / j.solmat.2019.02.015. [8] Li, P.; Liu, B.; Ni, Y.; Liew, K. K.; Sze, J.; Chen, S.; Shen, S.Large-Scale Nanophotonic Solar Selective Absorbers for High-Efficiency SolarThermal Energy Conversion. Adv Mater 2015, 27 (31), 4585-4591. DOI: 10.1002 / adma.201501686From NLM PubMed-not-MEDLINE. [9] Li, S. X.; Xu, Y. S.; Li, C. L.; Guo, Q.; Wang, G.; Xia, H.;Fang, H. H.; Shen, L.; Sun, H. B. Perovskite Single-Crystal Microwire-ArrayPhotodetectors with Performance Stability beyond 1 Year. Adv Mater 2020, 32(28), e2001998. DOI: 10.1002 / adma.202001998From NLM PubMed-not-MEDLINE.

[10] Lin, K.-T.; Nian, X.; Li, K.; Han, J.; Zheng, N.; Lu, X.; Guo,C.; Lin, H.; Jia, B. Highly efficient flexible structured metasurface byroll-to-roll printing for diurnal radiative cooling. eLight 2023, 3 (1). DOI:10.1186 / s43593-023-00053-3.

[11] Liu, V.; Fan, S. S4 : A free electromagnetic solver for layeredperiodic structures. Computer Physics Communications 2012, 183 (10), 2233-2244.DOI: 10.1016 / j.cpc.2012.04.026.

[12] Liu, Y.; Liu, R.; Qiu, J.; Wang, S. 4D printing of thermalresponsive structure for environmentally adaptive radiative cooling andheating. Journal of Advanced Manufacturing and Processing 2021, 4 (2). DOI:10.1002 / amp2.10107.

[13] Lu, Y.; Chen, Z.; Ai, L.; Zhang, X.; Zhang, J.; Li, J.; Wang,W.; Tan, R.; Dai, N.; Song, W. A Universal Route to Realize Radiative Coolingand Light Management in Photovoltaic Modules. Solar RRL 2017, 1 (10). DOI:10.1002 / solr.201700084.

[14] Qarony, W.; Hossain, M. I.; Dewan, R.; Fischer, S.; Meyer‐Rochow, V. B.; Salleo, A.; Knipp, D.; Tsang, Y. H. Approaching Perfect LightIncoupling in Perovskite and Silicon Thin Film Solar Cells by Moth EyeSurface Textures. Advanced Theory and Simulations 2018, 1 (8). DOI: 10.1002 / adts.201800030.

[15] Qing, Y. M.; Wang, H.; Lei, D. Wide-angle ultrabroadbandabsorption in black phosphorus / dielectric multilayer anisotropicmetamaterials. Journal of Optics 2024. DOI: 10.1088 / 2040-8986 / ad3cee.

[16] Song, J.; Seo, J.; Han, J.; Lee, J.; Lee, B. J. Ultrahighemissivity of grating-patterned PDMS film from 8 to 13 μm wavelengthregime. Applied Physics Letters 2020, 117 (9). DOI: 10.1063 / 5.0017838.

[17] Song, J.; Si, M.; Cheng, Q.; Luo, Z. Two-dimensional trilayergrating with a metal / insulator / metal structure as a thermophotovoltaicemitter. Appl Opt 2016, 55 (6), 1284-1290. DOI: 10.1364 / AO.55.001284From NLMPubMed-not-MEDLINE.

[18] Wang, T.; Wu, Y.; Shi, L.; Hu, X.; Chen, M.; Wu, L. A structuralpolymer for highly efficient all-day passive radiative cooling. Nat Commun 2021, 12 (1), 365. DOI: 10.1038 / s41467-020-20646-7From NLM PubMed-not-MEDLINE.

[19] Wu, D.; Liu, C.; Xu, Z.; Liu, Y.; Yu, Z.; Yu, L.; Chen, L.; Li,R.; Ma, R.; Ye, H. The design of ultra-broadband selective near-perfectabsorber based on photonic structures to achieve near-ideal daytime radiativecooling. Materials & Design 2018, 139 , 104-111. DOI: 10.1016 / j.matdes.2017.10.077.

[20] Zhang, H.; Ly, K. C. S.; Liu, X.; Chen, Z.; Yan, M.; Wu, Z.;Wang, X.; Zheng, Y.; Zhou, H.; Fan, T. Biologically inspired flexiblephotonic films for efficient passive radiative cooling. Proc Natl Acad Sci US A 2020, 117 (26), 14657-14666. DOI: 10.1073 / pnas.2001802117From NLM PubMed-not-MEDLINE.

[21] Zhou, J.; Chen, T. G.; Tsurimaki, Y.; Hajj-Ahmad, A.; Fan, L.; Peng, Y.; Xu, R.; Wu, Y.; Assawaworrarit, S.; Fan, S.; et al. Angle-selective thermal emitter for directional radiative cooling and heating. Joule 2023. DOI:10.1016 / j.joule.2023.10.013.

[22] Zhu, L.; Raman, A.; Wang, K. X.; Anoma, M. A.; Fan, S. Radiative cooling of solar cells. Optica 2014, 1 (1). DOI: 10.1364 / optica.1.000032.

[23] Zou, C.; Ren, G.; Hossain, M. M.; Nirantar, S.; Withayachumnankul, W.; Ahmed, T.; Bhaskaran, M.; Sriram, S.; Gu, M.; Fumeaux, C. Metal-Loaded Dielectric Resonator Metasurfaces for Radiative Cooling. Advanced Optical Materials 2017, 5 (20). DOI: 10.1002 / adom.201700460.

[24] Chae, D., Kim, M., Jung, P. H., Son, S., Seo, J., Liu, Y., ...& Lee, H. (2020). Spectrally selective inorganic-based multilayer emitter for daytime radiative cooling. ACS applied materials & interfaces, 12(7), 8073-8081. Summary of the Invention Therefore, one aspect of the present invention provides a patterned radiator comprising a polymer film and a first microscale surface structure formed on the polymer film.

[0006] Preferably, the polymer film is made of polydimethylsiloxane (PDMS).

[0007] In one implementation, the first microscale surface structure includes multiple micropyramids.

[0008] Preferably, the base angle of each micro pyramid is equal to or greater than 54.75°.

[0009] In a variation of the preferred embodiment, the patterned radiator is adapted to achieve an infrared emissivity greater than 0.95 within an atmospheric window.

[0010] In another variation of the preferred embodiment, the thickness of the patterned radiator is 200 micrometers or less.

[0011] More preferably, in some embodiments, the thickness of the radiator is 100 micrometers or less.

[0012] In another variation of the preferred embodiment, the radiator is flexible and stretchable.

[0013] According to another aspect of the present invention, a method for manufacturing a mold for a patterned radiator is provided. The method includes the steps of: manufacturing a mold comprising a second microscale surface structure using a 3D printing process; and performing a surface treatment on the mold to reduce demolding force.

[0014] Preferably, the second microscale surface structure comprises multiple inverted micropyramids.

[0015] In one embodiment, the 3D printing process described above is projection micro-stereolithography (PμSL).

[0016] In a variation of the preferred embodiment, FOTS (1H,1H,2H,2H-perfluorooctyltriethoxysilane) is used in the surface treatment step.

[0017] According to another aspect of the present invention, a method for manufacturing a patterned heat sink is provided. The method includes the steps of: providing a mold comprising a plurality of second microscale surface structures, spin-coating a degassed prepolymer onto the mold, and curing and separating the patterned heat sink from the mold.

[0018] Preferably, the degassed prepolymer is a degassed PDMS prepolymer.

[0019] Alternatively or additionally, the degassed PDMS prepolymer is mixed with the base material and curing agent.

[0020] Another aspect of the invention provides a high-performance patterned heat sink comprising a polymer film and a microscale surface structure with a variable cross-section design. This heat sink exhibits an emissivity close to 1 in the long-wave infrared spectrum (8–13 μm) and is capable of achieving wide-angle thermal radiation performance.

[0021] In some embodiments, the microscale structure is fabricated using 3D-printed molds, whose design parameters (including grating period, width, and height) are optimized to enhance emissivity.

[0022] In some embodiments, microscale surface structures can reduce impedance mismatch between air and heat sink material, thereby reducing reflectivity and improving absorption efficiency.

[0023] In some embodiments, the cavity resonance effect induced by the pyramid geometry enhances electromagnetic wave absorption in regions with low extinction coefficients, thereby further improving thermal radiation efficiency.

[0024] In some embodiments, the polymer material exhibits high long-wave infrared absorption characteristics due to its molecular structure.

[0025] In some embodiments, the manufacturing process includes: preparing a mold with a micro pyramid structure using a micron- or nanon-scale 3D printing process; surface-treating the mold to reduce demolding force; spin-coating a degassed prepolymer onto the mold; and curing and separating the patterned PDMS film to form a radiator.

[0026] In some embodiments, the radiator enhances heat dissipation by increasing spectral and angular emissivity, thereby providing efficient heat dissipation in compact systems.

[0027] In some embodiments, the surface design mitigates the effects of environmental thermal interference by stabilizing thermal radiation performance.

[0028] In some embodiments, the patterned radiator also includes a superhydrophobic surface treatment to enhance its durability and functionality under harsh environmental conditions.

[0029] Therefore, exemplary embodiments of the present invention provide a high-performance patterned heat sink with an emissivity close to 1 and excellent angular performance by forming a micro-pyramid surface structure on a polymer film. This design effectively solves the problems of impedance mismatch and low absorption efficiency in the long-wave infrared (LWIR) wavelength (8–13 μm) – commonly referred to as the atmospheric window. Its goal is to maximize the emissivity within the atmospheric window over the widest possible viewing angle. Projection micro-stereolithography (PμSL) is employed as a microscale 3D printing technology due to its high resolution from 0.6 μm to 30 μm and its relatively large printing area of ​​approximately 90 mm × 50 mm. PμSL's high planar resolution and layered manufacturing characteristics endow it with excellent processing accuracy and complexity, thus providing a high degree of design freedom. The surface structure was optimized through rigorous coupled-wave analysis (RCWA), and suitable dimensions were selected for PμSL processing. The prepared samples exhibited an emissivity close to 1 (>0.99) within the atmospheric window and maintained high emissivity over an angular range of 0°–80°. Experiments show that integrating a large-angle near-unit emissivity thermal radiator into an LED lighting system can significantly reduce its temperature and increase its brightness, demonstrating the application prospects of the LANE-RC (large-angle near-unit emissivity radiative cooler) research results in the field of thermal management of electronic devices.

[0030] The above summary is not intended to define the invention of this application (the scope of which is defined by the claims), nor is it intended to limit the scope of the invention in any way. Attached Figure Description

[0031] The above-described features and further features of the present invention will become apparent from the following description of embodiments, which are provided by way of example only in conjunction with the accompanying drawings, wherein: Figure 1a A schematic diagram illustrating key features of the LANE-RC according to an embodiment of the present invention is shown.

[0032] Figure 1b The emissivity of the structured PDMS film is shown to be related to the unit width and tilt angle (α).

[0033] Figure 2a This is a schematic diagram of the LANE-RC preparation process.

[0034] Figure 2b The water contact angles of ordinary PDMS and LANE-RC are shown.

[0035] Figure 2c A scanning electron microscope image of the LANE-RC surface at the first observation angle is shown, with a resolution of 100 μm.

[0036] Figure 2dA scanning electron microscope image of the LANE-RC surface at a second observation angle is shown, with a resolution of 100 μm.

[0037] Figure 2e A scanning electron microscope image of the LANE-RC surface at a second viewing angle is shown, with a resolution of 20 μm.

[0038] Figure 3a The measured emissivity of ordinary PDMS and LANE-RC films is shown.

[0039] Figure 3b The complex refractive index of PDMS is shown.

[0040] Figure 3c A schematic diagram illustrating the anti-reflective properties of the surface structure is shown.

[0041] Figure 3d1 This is a schematic diagram of the cross-sectional location of the surface structure.

[0042] Figure 3d2 The electric field distribution of the surface structure at a wavelength of ~9.5 μm is shown.

[0043] Figure 3d3 The electric field distribution of the surface structure at a wavelength of approximately 10.2 μm is shown.

[0044] Figure 3d4 The electric field distribution of the surface structure at a wavelength of approximately 12.5 μm is shown.

[0045] Figure 3e The emissivity as a function of azimuth angle was shown. and polar angle The relationship of change, that is .

[0046] Figure 3f The apparent temperatures of LANE-RC at different azimuth angles are shown, with the sample temperature kept constant at 35°C. (The lower the apparent temperature, the lower the emissivity).

[0047] Figure 4a This is a schematic diagram of the experimental setup for passive heat dissipation testing of LANE-RC in LED lighting applications.

[0048] Figure 4b The temperature curves of two sets of samples over time are shown. The right side of the figure is a magnified view of the colored area on the left.

[0049] Figure 4c The figure shows the illuminance curves of two sets of samples as a function of testing time. The right side of the figure is a magnified view of the colored area on the left. Detailed Implementation

[0050] As mentioned above, thermal management is a crucial aspect of the modern electronics industry, determining the extent of integration, multifunctionality, and miniaturization achievable by electronic devices. With the continuous improvement of electronic product performance and the constant reduction in power consumption, effective thermal management has become increasingly important. Outdoor electronic devices, in particular, face significant operating temperature differences and harsh environmental conditions, necessitating the development of efficient, reliable, and compact heat dissipation technologies.

[0051] Therefore, the first embodiment of the present invention proposes a thermal radiator characterized by a long-wave infrared emissivity close to 1, extremely low angular sensitivity, and superhydrophobic properties. Using 3D printing technology, a thermal radiator with an omnidirectional long-wave infrared emissivity close to 1 and superhydrophobicity is manufactured, specifically for thermal management of outdoor electronic devices. Its radiation characteristics combined with wide-angle high emissivity not only achieve a significant temperature reduction exceeding 23°C but also increase the brightness of lighting LEDs by 23.6%. These research results provide a new approach to thermal management of outdoor electronic devices and broaden the range of fabrication options for long-wave infrared functional devices.

[0052] This high-performance heat sink features patterned microscale structures on a flexible polymer film, such as... Figure 1a As shown, this heat sink achieves an emissivity close to 1 within an atmospheric window (8–13 μm), making it extremely efficient in thermal radiation management. This microscale structure addresses impedance mismatch and enhances light-trapping capabilities, thereby improving absorption and emission efficiency in both high and low extinction coefficient regions. Key features of this radiator include: • Enhanced radiative heat dissipation: This radiator significantly reduces thermal resistance by increasing hemispherical and spectral emissivity, providing superior cooling performance based on the principle of thermal radiation.

[0053] • Wide-angle performance: The angular insensitivity of emissivity ensures effective operation at different incident angles, and optimizes thermal management even in dynamic environments.

[0054] Durability and process scalability: Polymer-based membrane materials combine flexibility and chemical stability, and can be adapted to a variety of processing technologies, including precision 3D printing for structural optimization.

[0055] Compared with existing technologies / products, the advantages of this heat sink include, but are not limited to, the following: Near-unit emissivity over a wide angle range ● Patterned microscale structures achieve near-unit emissivity within an atmospheric window (8–13 μm), surpassing traditional planar or constant cross-section designs. Their ability to maintain high emissivity over a wide viewing angle enhances thermal radiation efficiency under diverse operating conditions.

[0056] • Enhanced heat dissipation performance through advanced mechanisms ● The microscale structure effectively reduces the impedance mismatch in the high extinction coefficient region, thereby minimizing reflection and maximizing absorption.

[0057] ● In regions with low extinction coefficients, this structure promotes cavity resonance, thereby improving absorption efficiency.

[0058] These mechanisms offer superior radiative cooling performance compared to existing planar or resonant designs alone.

[0059] • Scalability and customization based on flexible polymer materials ● Unlike rigid materials such as etched silicon, the use of polymer films offers flexibility, durability, and chemical resistance. Furthermore, this design supports scalable manufacturing processes, including precision 3D printing, allowing for customization for a wide range of applications.

[0060] • Improved performance stability and thermal shock resistance ● This heatsink not only dissipates heat more effectively but also increases heat capacity, thereby stabilizing the temperature in dynamic environments. This feature alleviates problems such as thermal shock commonly found in traditional solutions, improving the overall system reliability.

[0061] • Compact and lightweight design ● Unlike traditional bulky cooling systems, this thin and lightweight structure can be integrated into compact devices without compromising cooling performance. This advantage is crucial for portable or space-constrained applications.

[0062] • Versatility across application scenarios ● Typical embodiments of the present invention can adapt to diverse thermal management needs in industrial, optical, and outdoor systems. Its broad applicability contrasts sharply with existing technologies—which are often tailored to specific use cases or require specialized materials.

[0063] • Cost-effective manufacturing ● The combination of polymer materials and 3D printing technology significantly reduces production costs compared to traditional methods such as silicon etching. This makes the large-scale deployment of this invention economically feasible.

[0064] By overcoming the limitations of existing technologies with advanced emissivity, scalability, and stability, this radiator provides an excellent solution for efficient and versatile thermal management.

[0065] Therefore, this heatsink provides a versatile, scalable, and high-performance solution to the thermal management challenges faced in various fields. Applications of this heatsink include, but are not limited to: • Thermal management in harsh environments: The device can efficiently dissipate heat while withstanding extreme temperature differences, making it suitable for outdoor systems exposed to harsh climatic conditions.

[0066] • Compact thermal management system: Its lightweight and flexible design allows it to be integrated into compact devices, improving efficiency without increasing the overall size.

[0067] • Enhanced system stability: By maintaining stable thermal performance, this invention supports applications sensitive to temperature fluctuations, thereby improving overall system reliability.

[0068] • Scalable manufacturing for diverse applications: Flexible manufacturing methods allow for customization for a wide range of industrial, medical, and optical applications.

[0069] like Figure 1b As shown, a two-dimensional grating is fabricated on a polydimethylsiloxane (PDMS) film. Figure 1b In the diagram, high emissivity regions are highlighted on the far right with a rectangular dark outline, while structures fabricated via silicon etching are indicated by light-colored stripes. PDMS possesses numerous advantages, including flexibility, chemical inertness, biocompatibility, and ease of processing, making it suitable for medical, optical, electronic, and other fields. Due to its high Si-O-Si covalent bond content, PDMS exhibits high absorption in the 8-13 μm wavelength range (the well-known atmospheric window), making it an ideal material for this study. The surface structure used in this embodiment is a micro-pyramid, a structure widely used in the light-harvesting industry to improve photovoltaic conversion efficiency. A three-dimensional schematic diagram of the unit structure is shown below. Figure 1a As shown. In this exemplary embodiment, four design parameters are employed, namely the grating period ( Λ ), grating width ( w g ) and grating height ( t g To optimize the luminescence performance of LANE-RC. Λ It was determined to be 26 μm. w g It is 24 μm. t g The diameter is 25 μm. These structural parameters were determined using rigorous coupled-wave analysis (RCWA) at a wavelength of 10 μm. Typically, the pyramid structure is fabricated by pattern transfer from an alkaline-etched silicon mold. Due to the crystallographic properties of silicon, the base angles of the pyramid are fixed at 54.75°, which means... t g / w g The ratio is strictly defined. For example... Figure 3cAs shown, thermal radiators manufactured using traditional processes cannot achieve the ideal emissivity, while LANE-RC breaks through the limitations of unit aspect ratio and achieves a higher emissivity.

[0070] Based on the above structure, such as Figures 2a-2e As shown, a high-emissivity patterned thermal radiator named LANE-RC was fabricated using a 3D-printed mold. The mold was prepared using the PμSL 3D printing process with a BMF S130 printer, achieving an exposure accuracy of 2μm and a minimum layer thickness of 5μm. Through five-layer exposure, an inverted pyramid structure was formed on the 3D-printed mold, resulting in a blocky structure with an approximate inverted pyramid shape. Figure 2a Before the replication process began, the mold surface was treated with FOTS (1H,1H,2H,2H-perfluorooctyltriethoxysilane) to reduce demolding force. Subsequently, the degassed PDMS prepolymer was mixed with alkali and curing agent (Sylgard 184, DowCorning) at a ratio of 10:1 (by weight), poured onto the mold, and spin-coated to form a film approximately 100 μm thick. This film was then cured on a hot plate at 70°C for two hours. Finally, the LANE-RC film was separated. Figures 2b-2e show the surface morphology of the LANE-RC, indicating that the micropyramids were well-prepared and highly consistent in shape. Each pyramid exhibits an approximately cube-like appearance, but the cube shape is not as sharp as designed, mainly due to two reasons. First, the light modulated by the DMD (Digital Micromirror Device) diffracts at the edges, causing a slight deviation between the image projected onto the resin during 3D printing and the digital mask, thus blurring the outer contour of the printed mold. Second, the vacuum level during the PDMS molding process has an effect. Numerous studies have shown that vacuum level affects the adhesion between PDMS and the mold, thus directly influencing the morphology of the resulting PDMS structure. Surface smoothing treatment makes the prepared surface structure closer to the ideal pyramid structure.

[0071] The emission characteristics of LANE-RC were characterized using the integrated sphere method combined with Fourier transform infrared spectroscopy (FTIR). The LANE-RC sample was placed on an aluminum plate, and its reflectance was directly measured using FTIR. Clearly, the absorptivity, reflectance, and transmittance of the material follow the following pattern: (1) in A , R and T These represent absorptivity, reflectivity, and transmittance, respectively. Aluminum plates have high reflectivity and almost no transmittance in the infrared spectrum, therefore... TThis can be considered as 0. Furthermore, according to Kirchhoff's law of thermal radiation, under thermal equilibrium conditions, the thermal radiation absorptivity and emissivity of an object are strictly equal. Therefore, the absorptivity can be obtained by measuring the reflectivity of the sample. The emissivity of the sample is then compared to that of an approximate blackbody—modeled as a classic aperture in a cavity—to obtain the actual thermal radiation curve at room temperature. The thermal radiation curve is shown below. Figure 3a As shown, the blue background represents the atmospheric window, indicating the atmospheric transmission characteristics. The results show that LANE-RC exhibits a higher overall emissivity within the atmospheric window (8–13 μm), with an emissivity of 99.1% in this region, compared to only 95.2% for a conventional PDMS film of the same thickness. In the 8–13 μm wavelength range, the conventional PDMS film shows valleys near 9–10 μm and 12–13 μm, and a depression in the 10–11 μm region.

[0072] like Figure 3b As shown, the imaginary part of the refractive index (i.e., the extinction coefficient) k The extinction coefficient rises sharply near 9–10 μm and 12–13 μm. This larger extinction coefficient leads to a significant impedance mismatch between air and PDMS, thus enhancing reflectivity in these two bands and causing two valleys. The lower extinction coefficient in the 10–11 μm band results in relatively weaker absorption / emission characteristics. Electromagnetic waves in this band cannot be completely absorbed, forming the depression. In summary, in the high extinction coefficient band, although the material has strong absorption properties and electromagnetic waves can be absorbed over short distances, the interface reflectivity is high due to impedance mismatch with free space. In the low extinction coefficient band, electromagnetic waves can more easily penetrate the material, but the material's absorption efficiency is low and they cannot be completely absorbed. The surface pyramid structure on LANE-RC addresses these two problems sequentially through multiple mechanisms.

[0073] For large k In this region, reducing impedance mismatch is essential. The pyramid structure here is highly effective at reducing reflections. Due to the sloping surface of the pyramid structure, the propagation direction of incident light is deflected and interacts with the air-medium interface. Each time light incident, its energy is absorbed. In high... k In this region, light can be effectively absorbed at the surface, resulting in a large electric field gradient from the surface to the center, with the electric field at the center approaching zero. This multiple scattering effect greatly suppresses reflection, while the increase in transmitted light is due to the inherent high absorption characteristics of PDMS in this band, allowing these additional incident light to be efficiently absorbed internally. Furthermore, as... Figures 3d1-3d4The variable cross-section feature shown creates a transition zone between the air and the medium in terms of the electric field distribution at the cone cross-section, thereby generating a smooth refractive index gradient, alleviating the impedance mismatch between the medium and the air, and reducing reflection.

[0074] Besides the anti-reflective properties of LANE-RC, other mechanisms also affect the small k The absorption behavior in the regions (i.e., 9–10 μm and 12–13 μm). The corresponding electric field distribution is as follows. Figure 3f As shown, the electric field within the pyramid unit is clearly enhanced at wavelengths of approximately 8.2 μm and 10 μm, but the electric field density at approximately 9.5 μm is much lower than in free space. Electromagnetic waves entering the medium will continue to propagate within it and interact with it simultaneously. The enhancement of the electric field at wavelengths of 8.2 μm and 10 μm is mainly attributed to cavity resonance. The gradient lateral size characteristics of the pyramid structure bring about unique resonant response features, giving the entire structure a good cavity resonance effect over a wide wavelength range. This effect can significantly enhance electromagnetic wave absorption in the surface region. For the 9.5 μm wavelength, the electric field intensity decreases rapidly with increasing depth from the surface, and no significant resonance enhancement effect is observed. This is mainly due to the penetration depth of PDMS. δ λ Smaller. Penetration depth is defined as the electromagnetic radiation intensity attenuating to 1 / of its original value. e The depth at which penetration occurs. The penetration depth is calculated using the following formula:

[0075] in Let be the extinction coefficient. Clearly, a larger extinction coefficient indicates a smaller penetration depth, which means higher absorption efficiency. Due to this high absorption efficiency, the penetration depth at a wavelength of 9.5 μm is much smaller than that at wavelengths of 8.2 μm and 10 μm. Therefore, even though the conditions for cavity resonance are met at this wavelength, the strong absorption of electromagnetic waves at that wavelength by the PDMS prevents the generation of an electric field enhancement at the center of the pyramid unit.

[0076] Other wavelength bands are less affected than the atmospheric window band. In the 5μm to 8μm wavelength range, the absorptivity and emissivity of LANE-RC are still stronger than those of planar PDMS, but the emissivity has not yet reached a level close to 1. This is mainly due to the mismatch between the pyramid structure and the light wavelength; its scattering and resonance effects are significantly weaker than those in the atmospheric window band. This characteristic can reduce the impact of the surrounding thermal environment on the thermal radiator and improve the actual cooling performance of the thermal radiator.

[0077] Obviously, the formula for calculating the cooling power of a heat radiator is:

[0078] in , , These represent the heat power from atmospheric thermal radiation, daytime solar radiation, and environmental conduction and convection, respectively. The radiant power of the thermal radiator is given by the following formula:

[0079] in Indicates temperature as And the wavelength is Blackbody radiance at that time. It refers to the spectrum and angular emissivity. It is the surface area of ​​the thermal radiator. equal

[0080] and It is from 0 to any angle between them, It is from 0 to Any angle between them.

[0081] higher This will directly increase the overall cooling power of the thermal radiator, while the spectral and angular emissivity are close to 1. Will Increase to the maximum value. For example... Figure 3c As shown, the emissivity within the hemispherical space is significantly higher than that of ordinary PDMS and pure resonant PDMS metasurfaces. Figure 3e As shown, when θ is less than approximately 78° and 82°, the emissivity of LANE-RC is higher than 0.95 and 0.90, respectively. (Spectral and angular emissivity) The emissivity is significantly higher than that of ordinary PDMS and pure resonant PDMS metasurfaces. Since the resonant conditions of two-dimensional gratings are highly sensitive to angle, their emissivity is difficult to maintain when the angle θ is large. Given that the pyramid structure exhibits excellent light-trapping performance over a wide angle range, and its variable cross-section characteristics show better resonant response over a wide frequency range than a constant cross-section, LANE-RC demonstrates superior high emissivity characteristics within a hemispherical space.

[0082] LANE-RC exhibits near-unit emissivity and is thin enough to be integrated into compact electronic products for heat dissipation. An experiment was designed to measure its cooling effect on lighting LEDs. The experimental setup and schematic diagram are shown below. Figures 4a-4c As shown. In Figure 4aIn this experiment, LED modules were adhered to an aluminum plate using thermal paste, and LANE-RC was installed on the other side of the aluminum plate to dissipate heat towards the sky. The control group had no material adhered to their aluminum plates. When an LED is working, 30% of its energy consumption is converted into heat. Excessive temperature not only affects the LED's efficiency but can even cause it to burn out. Typically, lighting LEDs require heat sinks several times larger than themselves for heat dissipation, increasing the overall size of the LED. Lighting is often essential for outdoor hiking, but the extra size and weight of traditional heat dissipation methods greatly affect portability. In this experiment, a layer of LANE-EC film was placed over an aluminum plate (which served as a heat sink), and the lighting LED was adhered to the underside of the aluminum plate using thermal paste. Figure 4c As shown. The heat generated by the LED is conducted to the aluminum plate, which absorbs some of the heat and conducts it to the LANE-RC film covering its upper surface. The LANE-RC film then radiates the heat to the outside space. Another set of devices without LANE-RC coverage serves as a control group. The modular LED experimental setup is placed on a plastic support, with a lux meter placed below the LED to measure illuminance. Temperature is measured using thermocouples placed on a heat sink. To minimize the effects of heat conduction and heat conversion, the connection between the device and the support is point contact, and the device is covered with an infrared-transparent PE layer. To avoid the influence of external light sources (i.e., architectural lighting in the experimental environment), the experimental setup is surrounded by a black cover, and the two sets of components are separated by a black plate to prevent mutual interference.

[0083] The results are as follows Figures 4b-4c As shown in the figure. During the test, the temperature of the LENC-RC group was significantly lower than that of the control group. The maximum temperature difference reached 23.8°C. Throughout the entire process, the illuminance of the LENC-RC installation group was higher than that of the control group, with the maximum illuminance increasing by 23.8%, as shown in the figure. Figure 4b As shown, this visually demonstrates that LENC-RC enhances LED lighting performance and provides significant temperature control. Furthermore, the addition of LENC-RC adds extra heat capacity to the system, helping to stabilize system temperature and illuminance. The inclusion of LENC-RC significantly improves temperature stability and lighting stability. In practical applications, the operating state of LEDs is affected by various factors, including environmental factors such as wind, or system factors such as thermal shock caused by power instability. These effects can lead to transient fluctuations in lighting performance, causing LED flicker, reducing lighting quality, and impacting practical use. In this situation, LANE-RC can continuously dissipate heat, and its additional heat capacity can mitigate the adverse effects of thermal shock, thereby improving overall lighting quality. This experiment demonstrates that LANE-RC has great potential in the field of thermal management for electronic devices, mainly due to its emissivity, which is close to 1 within the atmospheric window and has a wide angular range.

[0084] In summary, the above exemplary embodiments, utilizing micro-3D printing technology, provide a LANE-RC heatsink with near-unit emissivity (>0.99) within an atmospheric window. This heatsink combines the excellent light-trapping performance of its surface pyramid structure with its weak angle dependence, achieving ultra-high emission performance over a wide range within a hemispherical space. Furthermore, this paper experimentally evaluates its cooling performance, finding that the heatsink not only significantly reduces the operating temperature of lighting LEDs by 23.8°C but also increases the brightness of lighting LEDs by approximately 24% and improves their operating efficiency. This result demonstrates the broad application prospects of LANE-RC in the field of radiative cooling for electronic devices and also proves the feasibility of applying micro-3D printing technology in the field of high-performance radiative cooling.

[0085] The main features of LANE-RC include, but are not limited to: • Micro-pyramid surface structure: The variable cross-section pyramid design minimizes reflectivity, maximizes absorption efficiency through cavity resonance, and enhances emissivity over a wide range of incident angles.

[0086] • Material optimization: Suitable materials with high absorption rate, flexibility and chemical stability in the long-wave infrared (LWIR) band should be selected.

[0087] Manufacturing Process: A 3D-printed mold with a near-inverted pyramid structure is used to form the polymer film. Depending on the application, the heat sink can be directly manufactured via 3D printing. The achieved precision ensures the reproduction of high-performance surface structures.

[0088] • Enhanced thermal radiation performance: This radiator exhibits near-uniform emissivity (99.1%) within the atmospheric window, significantly outperforming ordinary polymer films.

[0089] Other innovative features related to LANE-RC include, but are not limited to: • Surface geometry innovation: The micro-pyramid structure reduces impedance mismatch by providing a gradual refractive index transition, ensuring enhanced electromagnetic wave coupling.

[0090] • Wide viewing angle performance: The variable cross-sectional geometry provides high emissivity over a wide viewing angle, making the radiator suitable for various environmental orientations.

[0091] • Enhanced cavity resonance: By utilizing the geometric resonance effect, this structure improves absorption and emission efficiency in specific long-wave infrared (LWIR) bands (especially in the high extinction coefficient region).

[0092] • Simplified manufacturing process: An innovative approach combining 3D printed molds with FOTS surface treatment ensures accurate replication and scalability.

[0093] The exemplary embodiments have now been fully described. Although the specification refers to specific embodiments, those skilled in the art will clearly recognize that the invention can be practiced with variations in these specific details. Therefore, the invention should not be construed as being limited to the embodiments described herein.

[0094] While various embodiments have been shown and described in detail in the accompanying drawings and the foregoing description, they should be considered illustrative rather than restrictive. It should be understood that exemplary embodiments have only been shown and described, and the scope of the invention is not limited in any way. It is understood that any feature described herein can be used in conjunction with any embodiment. The exemplary embodiments are not mutually exclusive, nor are they exclusive of other embodiments not mentioned herein. Therefore, the present invention also provides embodiments comprising combinations of one or more of the foregoing exemplary embodiments. Modifications and variations of the invention may be made without departing from the spirit and scope of the invention; therefore, only the limitations specified in the appended claims should be applied.

[0095] As used herein, the expression “and / or” referring to two or more elements should be interpreted as referring to only one element, or a combination of elements. For example, “element A, element B, and / or element C” may include only element A, only element B, only element C, element A and element B, element A and element C, element B and element C, or all three of A, B, and C. Furthermore, “at least one of A or B” may include at least one of A, at least one of B, or at least one of A and at least one of B. Further, “at least one of A and B” may include at least one of A, at least one of B, or at least one of A and at least one of B.

[0096] The subject matter of this disclosure is specifically described herein to satisfy legal requirements. However, this description itself is not intended to limit the scope of this disclosure. Rather, the inventors believe that the claimed subject matter may also be embodied in other ways, including different steps or combinations of steps similar to those described herein, and in combination with other existing or future techniques. Furthermore, although terms such as “step” and / or “module” may be used herein to refer to different elements of the method employed, these terms should not be construed as implying any particular order between the various steps disclosed herein unless the order of the individual steps is explicitly described.

Claims

1. A patterned radiator, comprising: Polymer membranes, and The first microscale surface structure formed on the polymer film.

2. The patterned radiator of claim 1, wherein the polymer film is made of polydimethylsiloxane.

3. The patterned radiator of claim 1, wherein the first microscale surface structure comprises a plurality of micro pyramids.

4. The patterned radiator of claim 3, wherein the base angle of each of the micro pyramids is equal to or greater than 54.75°.

5. The patterned radiator of claim 1, wherein the patterned radiator is adapted to achieve an infrared emissivity greater than 0.95 within an atmospheric window.

6. The patterned radiator of claim 1, wherein the thickness of the patterned radiator is 200 micrometers or less.

7. The patterned radiator of claim 1, wherein the patterned radiator is flexible and stretchable.

8. A method for manufacturing a mold for a patterned radiator as described in claim 1, the method comprising the following steps: a) Use 3D printing technology to manufacture molds containing second-microscale surface structures; as well as b) Perform surface treatment on the mold to reduce demolding force.

9. The method of claim 6, wherein the second micron-scale surface structure comprises a plurality of inverted micropyramids.

10. The method of claim 6, wherein in step a), the 3D printing process is a projection micro-stereolithography process.

11. The method of claim 6, wherein in step b), FOTS (1H,1H,2H,2H-perfluorooctyltriethoxysilane) is used.

12. A method for manufacturing a patterned heat sink as claimed in claim 1, comprising the following steps: A mold comprising multiple second-microscale surface structures is provided; A degassed prepolymer is spin-coated onto the mold; as well as The patterned heat sink is cured and separated from the mold.

13. The method of claim 10, wherein the degassed prepolymer is a degassed PDMS prepolymer.

14. The method of claim 10, wherein the degassed PDMS prepolymer is mixed with an alkali and a curing agent.

Citation Information

Patent Citations

  • Improvement in lamp-burners

    US101073A